New carcharhiniform sharks (Chondrichthyes, Elasmobranchii) from the early to middle Eocene of Seymour Island, Antarctic Peninsula - Engelbrecht, Andrea; Mörs, Thomas; Reguero, Marcelo Alfredo; Kriwet, Jürgen (Journal of Vertebrate Paleontology)
Seymour Island, Antarctic Peninsula, is known for its wealth of fossil remains. This island provides one of the richest fossiliferous Paleogene sequences in the world. Chondrichthyans seemingly dominate this Eocene marine fauna and offer a rare insight into high-latitude faunas during the Palaeogene. So far, only a few isolated teeth of carcharhinid sharks have been reported from Seymour Island. Bulk sampling in the well-exposed La Meseta and Submeseta formations yielded new and abundant chondrichthyan material, including numerous teeth of carcharhinid and triakid sharks. Here, we present a reevaluation of the previously described carcharhinid remains and a description of new taxa: Meridiogaleus cristatus, gen. et sp. nov., Kallodentis rythistemma, gen. et sp. nov., Abdounia richteri, sp. nov., and Abdounia mesetae, sp. nov. The carcharhiniforms Mustelus sp. and Galeorhinus sp. are reported based on rare material, whereas teeth previously assigned to Scoliodon represent a nomen dubium. https://zoobank.org/urn:lsid:zoobank.org:pub:6FA3D201-3686-4129-BC09-10FC86E3DD34 Citation for this article: Engelbrecht, A., T. Mörs, M. A. Reguero, and J. Kriwet. 2017. New carcharhiniform sharks (Chondrichthyes, Elasmobranchii) from the early to middle Eocene of Seymour Island, Antarctic Peninsula. Journal of Vertebrate Paleontology. DOI:10.1080/02724634.2017.1371724. Fil: Engelbrecht, Andrea. Universidad de Viena; Austria Fil: Mörs, Thomas. Swedish Museum of Natural History; Suecia Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados; Argentina Fil: Kriwet, Jürgen. Universidad de Viena; Austria